In Connection With Mechanism of Very Low Frequency Electromagnetic Emission Generated in Seismoactive Zone - Kereselidze, Zurab A.; Kachakhidze, Nino K.; Kachakhidze, Manana K. (Journals of Georgian Geophysical Society, 2017)
By helping of model of analogous circuit, created with virtual linear conductors, it is possible to implement monitoring of earth electromagnetic emission of earthquake preparing process by frequency spectrum control. By model it is also possible to connect telluric by nature geoelectric and geomagnetic perturbations caused by rocks polarization with selfgenerated electromagnetic oscillations of lithosphere-atmosphere-ionosphere system. In case of quite reliable results of observed data diagnostic analyse, it is supposed that the analogous model will be useful by point of earthquake prediction problem.